Application of Revit Secondary Development in Sluice Seepage Calculation - NIU Lijun; LI Yihao (Renmin Zhujiang)
Based on the concept of forward design,this paper uses C# language to abstract and package the traditional seepage calculation method (improved resistance coefficient method) and redevelops AutoRevit through Revit API interface programming.As a result,the visual interactive analysis process of sluice seepage calculation is achieved so that the design of sluice anti-seepage measures can realize forward design based on a three-dimensional model.In this paper,a regulating sluice is taken as an example for verification,and the results are compared with those calculated by AutoBank software.The results show that the plug-in has high accuracy and efficiency and realizes the highly visual sluice seepage calculation and low-difficulty human-computer interaction.At the same time,it has the function of instantly judging the results according to the specification.The plug-in not only expands the function of BIM technology but also facilitates designers in the water conservancy industry.In addition,it provides certain technical references for further expanding the deep application of BIM technology in water conservancy design.